IMAGING PAEDIATRIC FACIAL INJURIES IN THE EMERGENCY DEPARTMENT. Issue 9 (14th August 2014) - Long, Linzie; Trivedy, Chet; Crossman, Richard J; Flowers, Ms Joanne; Cooke, Matthew W
Abstract : Objectives & Background: Facial injuries are a common presentation to the ED with data suggesting that this may be as high as 4%. There is little data on the epidemiology of paediatric facial injuries and how these are managed by the ED team. The exposure of structures such as the eyes, brain and thyroid to ionising radiation may be potentially harmful and at present there are no nationally agreed guidelines on which patients require imaging in the ED. The aim of this study was to look at the patterns of imaging in a cohort of paediatric facial injuries presenting to an ED in the West Midlands . Methods: A retrospective note review of all facial injuries presenting to any one of the three sites that make up the Heart of England NHS Foundation Trust in 2012 was conducted. Electronic records were examined to look for the mechanism of injury, disposal as well if any imaging had been performed during the initial presentation. Where imaging was performed the actual imaging as well as formal radiology reports were accessed to ascertain for the presence or absence of a facial fracture. Results: Paediatric facial injuries made up 1131/3416 (33%) of the overall number of facial emergencies presenting to the ED in 2012. The mean age for the children was 6.9±4.3 years. 32% of the children were female as opposed to 68% who were male. 164/1131(14.5%) children were imaged and of these only 17/164 (10.4%) were confirmed to have a fracture. In contrast 47% of the adults were imaged and 26% of these were confirmed to have a facial fracture. Chi-squared tests demonstrated that the proportion of patients who had imaging requested was significantly lower in the paediatric cohort when compared to adults (P<0.005). Also the difference in the numbers of confirmed facial fractures in those who were imaged was significantly lower in children when compared to the adults (P<0.005). Occipitomental (OM) and orthopantomograms (OPG) were the commonest facial views requested for both the paediatric and adult facial injuries. Conclusion: The study highlights that paediatric facial injuries are less common than adult facial injuries and that facial fractures make up only 1.5% of all paediatric facial injuries. Clinicians should consider this when requesting facial X-rays given the potential harm of ionising radiation to the head and neck region. Further studies are in progress to develop evidence based guidelines for imaging children with facial injuries within the ED. The table refers to the total number of different imaging requests and not the number of patients imaged. Some patients had more than one type of imaging requested.